RECEIVER FUNCTIONS APPLICATION FOR STUDYING THE DEEP STRUCTURE OF THE LENA DELTA REGION - Novikov, Mikhail; Krylov, Artem; Roginskiy, Konstantin (International Multidisciplinary Scientific GeoConference SGEM, 2024)
Receiver function analysis is a critical tool in seismology, used to study the deep structure of the crust and upper mantle. Information about the deep structure of the crust and seismicity is important initial data for developing a source model and seismic hazard assessment. The presence of sharp discontinuities beneath the monitoring station induces the generation of converted body waves, which propagate at slower velocities than those of the primary P-wave. Receiver function analysis utilizes the lag between the arrival times of converted waves to estimate the depths of interfaces. Furthermore, by using various inversion algorithms, including receiver function inversion and surface wave group velocity inversion, a shear wave velocity model under the station can be inferred. This study seeks to examine the depth-velocity structure of the Lena Delta by analyzing receiver functions and surface-wave data. Receiver function analysis was performed using waveforms from the TIXI station, a component of the Yakutsk Regional Seismic Network of the Russian Federation. For the analysis, 245 large earthquakes (M1 > 7) occurring between 2000 and 2024, and located at distances ranging from 20° to 100° from the station, were initially selected. The iterative deconvolution was then used to obtain radial and transverse receiver functions. Three different inversion algorithms were used to attain the velocity model: receiver function inversion (rftn96), Rayleigh group wave velocity inversion (surf96), and joint inversion (joint96). A wide peak lasting from 3 to 5 seconds after the initial P-wave arrival and a sharp peak at 7.5 seconds were observed on the radial receiver function. The presence of two distinct peaks complicates the application of conventional H-k stacking analysis, which assumes a single discontinuity. Rayleigh wave group velocity inversion only showed one sharp increase in shear wave velocity at 15 km, while both receiver function inversion and joint inversion showed step-like increases at 15, 30, and 40 km, which indicates the presence of layer boundaries at these depths. The obtained values are consistent with existing data on the region, including deep seismic sounding profiles and crustal models. Previous research, along with the findings of this study, indicates that 15 km is most likely the boundary between the upper and the lower crust, 30 km is a transition to the anomalous mantle, and 40 km is the Moho boundary.